Pengembangan Potensi Desa Di Kecamatan Slahung Dengan Reaktivasi Jalur Exsisting Madiun - Slahung - Zulkarnain, Akbar; Budi, Hari; Priwardana, Faizal Riko (Indonesian Railway Journal, 2017)
Slahung Subdistrict in Ponorogo  District,  East  Java  Province, has  great  potency  in  agriculture.  Most of the crops can not be utilized optimally for  economic  growth  in  the  Sub-district  due  to limited access of roads, therefore the study analised  development  of  trains  for  optimizing  the  potency of Slahung by using literature study and field survey  along  the  existing  route  Madiun- Slahung. Data was collected from the Slahung District Office and from a  survey  of  railway conditions along the track. The results obtained  are (1) Comparison of energy  consumption  shows  that train is superior at Rp 14, 87 Km / ton and 0.0025 liter / km / ton for freight transport. (2) By utilizing paddy and sugar cane production in Slahung area, Slahung will earn a profit of Rp 2,468,542,182,850.00 per year when selling the  crop  in  Madiun  City.  (3)  The  survey  estimates that 61% of the Madiun -  Slahung railway line  in good  condition and  39% in poor condition,  some of the track located in the middle of agricultural land which will make it easier for farmers  to distribute their harvest to the trading center.  (4)  The  survey  results  show  that  the  Slahung community needs a cheap and fast mode of transportation  that  overide  convenience  factor,  so  that the train with its characteristics can be accepted by the community.